PELAKSANAAN KEWAJIBAN PENGGARAP DALAM PERJANJIAN BAGI HASIL USAHA PERKEBUNAN KARET DI DESA PETAR DALAM KABUPATEN MUARA ENIM PROVINSI SUMATERA SELATAN - Sari, Anggela Novita; Firdaus, Firdaus; Putra, Setia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
The implementation of cooperation agreements for the production of rubber plantation land ismostly carried out in rural areas and is carried out verbally, as happened in Petar Dalam Village,Muara Enim Regency, South Sumatra Province. In carrying out this agreement, there are times whenproblems occur between the parties. Most of the problems in Petar Dalam village are caused bycultivators who are negligent in carrying out their obligations. Therefore, the purpose of this researchis to first examine the implementation of cultivator obligations in the rubber plantation businesscooperation agreement in Petar Dalam Village, Muara Enim Regency, South Sumatra Province.Second, settlement of disputes on the implementation of cultivator obligations in the rubber plantationbusiness cooperation agreement.This type of research can be classified as sociological research. The research location takesplace in Petar Dalam Village, Muara Enim Regency, South Sumatra Province, while the populationand sample are all parties related to the problem under study. This study uses data sources in the formof primary and secondary data, and data collection techniques are carried out through interviews.From the results of research problem, there are two things that can be concluded. From theresults of research problems there are two things that can be concluded. First, the implementation ofthe cultivator's obligations in the rubber plantation business agreement in Petar Dalam Village has abackground of beliefs and habits that have been carried out for a long time, as well as the rights andobligations of the cultivator and the owner, which were also spoken verbally when making anagreement, which led to several cases of neglect by cultivators in carrying out their obligations.Second, the settlement of disputes regarding the implementation of the cultivator's obligations in therubber plantation business cooperation agreement in Petar Dalam Village is amicable, namely byconducting deliberations of the parties, but if the deliberations do not reach a meeting point, theHeadman will be involved as a mediator. The author's suggestion is First, it is better if the owner andcultivator use a written agreement as the basis for entering into a production sharing cooperationagreement to ensure the fulfillment of the rights and obligations of the parties in entering into theagreement, and it is easy to prove if in the future there is a default by one of the parties. Second, it isbetter if, when entering into a production sharing agreement, the owner and cultivator involve theheadman and two witnesses so that the headman, as village apparatus, can also be the officialmediator in any disputes between the parties.Keywords: Agreement-Cooperation-Profit Sharing